Exploring the impact of pre-service science teachers' reflection skills on the development of professional knowledge during a field experience. Issue 18 (12th December 2021) - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph
ABSTRACT: The process of reflection is assumed to be important for developing professional knowledge through practical experience in science teaching. However, this claim requires more evidence, based on a clear definition of reflection. The main goal of the present study is to explore how reflection skills influence the development of professional knowledge gained through teaching experience. Before and after a five-month field experience, we have measured pre-service physics teachers' professional knowledge and reflection skills (N = 94; 133 cases pre and post from four German universities). We also collected data for learning opportunities during the field experience (e.g. the number of taught lessons). The present study uses a novel standardized digital simulation of collaborative oral reflections to measure reflection skills (performance assessment), as a way of increasing validity compared to self-reports. The data have been analyzed using path analysis. The main results show that reflection skills before a field experience impact the development of content knowledge ( β  = 0.231*) and pedagogical knowledge ( β  = 0.354**) during the field experience. Regarding the learning opportunities during the field experiences, we develop the following evidence-based post-hoc hypothesis: the more pre-service science teachers are enculturated into a community of practical teachers, the less (academic) content knowledge and pedagogical content knowledge they acquire during a field experience. Consequences for science teacher education will be discussed.